Cationic versus anionic Pt complex: The performance analysis of a hybrid-capacitor, DFT calculation and electrochemical properties. (1st January 2019) - Akkoç, Mitat; Demirel, Serkan; Öz, Erdinç; Altın, Serdar; Bayri, Ali; Dorcet, Vincent; Roisnel, Thierry; Bruneau, Christian; Özdemir, İsmail and Yaşar, Sedat
Graphical abstract: Ionic [PtCl3 (DMSO)] − [NHC] + complex used as a capacitor material. Abstract: The synthesis and characterization of cationic versus anionic platinum(II) complex of the type [PtCl3 (DMSO)] − [NHC] + (NHC: N -heterocyclic carbene) is reported for the first time. The complex3 was synthesized from silver(I)-NHC2, and K2 [PtCl4 ] in DMSO at 80 °C under exclusion of light. The ionic platinum(II) complex was obtained in high yield and fully characterized by 1 H, 13 C, 195 Pt NMR and HRMS spectroscopy, X-ray diffraction and elemental analysis. The structural properties of the complex were investigated by using Gaussian suit and the obtained parameters were crosschecked with the X-ray data. The HOMO-LUMO energies and electrostatic surface mapping of the complex were calculated and the results were discussed with the capacitive properties of the complex. Electrochemical analysis by cyclic voltammetry (CV) of the complex shows reversible redox peaks about platinum center. The complex was used as an electrode material for the capacitor device and result is promising that the highest performance of complex3 was found as 10.22 F/g.